The East Gotland Basin (Baltic Sea) as a candidate Global boundary Stratotype Section and Point for the Anthropocene series. (April 2023) - Kaiser, Jérôme; Abel, Serena; Arz, Helge W; Cundy, Andrew B; Dellwig, Olaf; Gaca, Pawel; Gerdts, Gunnar; Hajdas, Irka; Labrenz, Matthias; Milton, James A; Moros, Matthias; Primpke, Sebastian; et al.
The short sediment core EMB201/7-4 retrieved from the East Gotland Basin, central Baltic Sea, is explored here as a candidate to host the stratigraphical basis for the Anthropocene series and its equivalent Anthropocene epoch, still to be formalized in the Geological Time Scale. The core has been accurately dated back to 1840 CE using a well-established event stratigraphy approach. A pronounced and significant change occurs at 26.5 cm (dated 1956 ± 4 CE) for a range of geochemical markers including 239+240 Pu, 241 Am, fly-ash particles, DDT (organochlorine insecticide), total organic carbon, and bulk organic carbon stable isotopes. This stratigraphic level, which corresponds to a change in both lithology and sediment colour related to early anthropogenic-triggered eutrophication of the central Baltic Sea, is proposed as a Global boundary Stratotype Section and Point for the Anthropocene series.